2002
DOI: 10.1354/vp.39-1-120
|View full text |Cite
|
Sign up to set email alerts
|

MIB-1 Labeling Index in Feline Dysplastic and Neoplastic Mammary Lesions and Its Relationship with Postsurgical Prognosis

Abstract: Abstract. Samples from feline normal, dysplastic, and neoplastic mammary tissues were used to investigate the usefulness of MIB-1 labeling index (MIB-1 I) as a prognostic indicator. Forty-eight queens bearing invasive carcinomas were included in a 2-year follow-up study. Mammary lesions were classified according to the World Health Organization system, and invasive carcinomas were further graded on the basis of the degree of tubule formation, the degree of nuclear and cellular pleomorphism, and mitotic count. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 16 publications
6
58
0
8
Order By: Relevance
“…Comparing patterns in mammary carcinomas of zoo felids with those mammary carcinomas arising spontaneously or in progestin-treated domestic cats was not possible because mammary cancer in domestic cats was usually designated by the predominant pattern, and whether multiple patterns occurred was not generally reported. 5,8,13,14,26,28,33,42 Furthermore, tumor classification of mammary gland carcinomas in domestic cats has been inconsistently applied over the years, with tumors often either grouped as adenocarcinomas or subclassified by other patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing patterns in mammary carcinomas of zoo felids with those mammary carcinomas arising spontaneously or in progestin-treated domestic cats was not possible because mammary cancer in domestic cats was usually designated by the predominant pattern, and whether multiple patterns occurred was not generally reported. 5,8,13,14,26,28,33,42 Furthermore, tumor classification of mammary gland carcinomas in domestic cats has been inconsistently applied over the years, with tumors often either grouped as adenocarcinomas or subclassified by other patterns.…”
Section: Discussionmentioning
confidence: 99%
“…5,28,42 Percentage of tubule formation, mitotic count, and nuclear morphology were each assigned an individual score from 1 to 3 on the basis of the criteria listed in Table 1. Tubule formation score was based on the percentage (0-100%) of tumor tissue from the representative section in which clear tubule formation was present.…”
Section: Tumor Morphology Tumor Grade and Metastasismentioning
confidence: 99%
“…Comparative studies of the proliferative index (measured by Ki67/MIB1 expression) in feline fibroepithelial hyperplasia and other mammary tumours showed that, in spite of being a benign disturbance, it shows a very high proliferative index similar to the one observed in invasive mammary carcinomas [34,35]. Fibroepithelial hyperplasia, which exhibits unique morphological and biological features, is characterised by rapid proliferation of epithelium and stroma [35].…”
Section: Pathogenesis Of the Feline Mammary Fibroepithelial Hyperplasiamentioning
confidence: 99%
“…It should be remembered that mammary fibroepithelial hyperplasia lesions are highly proliferative [34,35] and that some degree of cytological atypia [21] are often described, which along with the described loss of cell polarity [17] and the occurrence of mitosis [17,31], can create a falsely malignant appearance that could biased the diagnosis. Consequently, if a histopathological diagnosis is wanted, an excisional biopsy is preferable to a fine needle aspiration, despite being more expensive.…”
Section: Diagnostic Endorsementsmentioning
confidence: 99%
“…Il est alors nécessaire de connaître les facteurs pronostiques afin de prévenir le devenir du patient et de mettre en place un plan thérapeutique adapté. Ceux utilisés dans le pronostic du cancer du sein sont également connus dans l'espèce féline : la taille tumorale (MacEwen et al 1984 ;Ito et al 1996 ;Viste et al 2002 ;Millanta et al 2005 a;Seixas et al 2011), la présence ou non de métastases ganglionnaires ou à distance (Weijer et al 1983 ;Ito et al 1996 ;Seixas et al 2011, Zapulli et al 2014, le type et le grade histologique du carcinome (Weijer et al 1983 ;Ito et al 1996 ;Castagnaro et al 1998 ;Millanta et al 2002 ;Seixas et al 2011 ;Segonzac, 2013 ;Zapulli et al 2014), le caractère complet de l'exérèse chirurgicale (Weijer et al 1983), le score d'expression du facteur de croissance épidermique de type 2 (HER2) (Millanta et al 2005b ;Rasotto et al 2011), l'expression des récepteurs des oestrogènes et de la progestérone (Millanta et al 2005b ;Millanta et al 2006) et l'invasion lymphovasculaire (Seixas et al 2011 ;Preziosi et al 2002 ;Tanabe et al 2002 ;Sarli et al 2003;Zapulli et al 2014).…”
Section: Introductionunclassified